IMPACTS THE BRAND OF EXPERIENCE AND BRAND IMAGE ON BRAND LOYALTY: MEDIATORS BRAND OF TRUST - Marliawati, Annisa; Cahyaningdyah, Dwi (Management Analysis Journal, 2020)
This study is to examine the effect of brand experience and brand image on brand loyalty through brand trust. The population of this study is Ijjah_Collection customer via Shopee in Indonesia. The sample of this study consisted of 116 respondents using non-probability method. The method of collecting the data used questionnaire roomates then Analyzed using path analysis with IBM SPSS Statistics 22 program. The results of this study Showed: (1) brand experience has a positive and significant effect on brand loyalty, (2) brand image has a positive effect, but is not significant on brand loyalty, (3) brand experience has a positive effect and signficant on brand loyalty through brand trust, (4) brand image has a positive and significant effect on brand loyalty through brand trust, (5) brand trust has a positive and significant effect on brand loyalty.